Pengaruh Gaya Hidup Berbelanja Dan Ketertarikan Fashion Terhadap Perilaku Pembelian Impulsif Online Shoping Mahasiswa STIE Dwi Sakti Baturaja - Sally Maria Bramana; Yuniarti Anwar; Inda Sartika (Jurnal Mirai Management, 2022)
Abstract This study aims to determine the effect of shopping lifestyle and fasion attraction on online shopping impulsive buying behavior (a case study on STIE Dwi Sakti Baturaja students). This research method uses descriptive method. The data analysis technique used in this study uses quantitative data analysis techniques. Based on the research results, it was found that the correlation coefficient value was R = 0.774 in the interval 0.60-0.79 meaning that the relationship between lifestyle (X₁) and fashion interest (X₂) on online shopping impulsive buying behavior (Y) is strong. The coefficient of determination R square is 0.598, this means that the influence of lifestyle variable (X₁) and fashion interest (X₂) on online shopping (Y) impulsive buying behavior is 59.8%, while the remaining 40.2% can be explained by factors which were not examined in this study. The results of the t test and F test show that lifestyle and fashion interest partially and simultaneously influence online shopping impulsive buying behavior among STIE Dwi Sakti students in Baturaja. Keywords: Shopping Lifestyle, Fashion Interest, and Impulsive Buying Behavior.